Perioperative management of a patient with retrosternal giant goiter and Gitelman syndrome: a case report - Dongdong Chen; Chen Li; Chengming Zhang; Wenwen Wang (Frontiers in Medicine, 2026)
Background Gitelman syndrome is an autosomal recessive renal tubular disorder caused by mutations in the SLC12A3 gene, with the pathogenic mechanism being impaired function of the thiazide-sensitive sodium-chloride cotransporter. The disease is mainly characterized clinically by hypokalemia, hypomagnesemia, metabolic alkalosis, and hypocalciuria. Retrosternal giant goiter is mostly caused by nodular goiter enlarging and extending downward into the anterior mediastinum, which may lead to tracheal compression and displacement. Patients with retrosternal giant goiter complicated with Gitelman syndrome often present with severe electrolyte disturbances and risk of difficult airway, and relevant literature reports are relatively rare. Case summary This article reports a 75-year-old male patient with Gitelman syndrome who was scheduled for thyroidectomy due to “retrosternal giant goiter causing left recurrent laryngeal nerve palsy.” Laboratory examination revealed severe hypokalemia, hypomagnesemia, hyponatremia, hypochloremia, and metabolic alkalosis. The supine hypertension panel showed significantly elevated renin activity. Ambulatory electrocardiography suggested frequent premature atrial contractions (>14,000 beats/24 h). Imaging revealed a huge mass in the left thyroid lobe (6.6 cm × 4.1 cm) extending into the mediastinum, compressing the trachea and esophagus, with right-sided aortic arch deformity. After multidisciplinary consultation and active correction of electrolyte disturbances, the patient successfully underwent left total thyroidectomy + recurrent laryngeal nerve exploration under general anesthesia. Key management points included: preoperative optimization of electrolytes to safe thresholds; avoidance of drugs that prolong the QT interval and affect electrolyte balance; intraoperative continuous electrocardiographic monitoring and electrolyte monitoring; and formulation of a difficult airway plan. The patient recovered well postoperatively without serious complications such as arrhythmias. Conclusion The perioperative management of retrosternal giant goiter complicated with Gitelman syndrome is highly challenging. In this case, adequate preoperative assessment, active correction of electrolyte disturbances to safe thresholds, rational selection of anesthetic agents, formulation of a difficult airway management plan, and close monitoring were associated with a favorable clinical outcome.